Regulation of expression of genes for light-harvesting antenna proteins LH-I and LH-II; reaction center polypeptides RC-L, RC-M, and RC-H; and enzymes of bacteriochlorophyll and carotenoid biosynthesis in Rhodobacter capsulatus by light and oxygen. - Zhu, Y S (1986)
RNA levels were measured by blot hybridization to study the coordinate and differential expression of Rhodobacter capsulatus genes for light-harvesting I antenna proteins LH-I and LH-II; reaction center (RC) polypeptides L, M, and H; and bacteriochlorophyll and carotenoid biosynthesis in response to light and O2. The genes for LH-II alpha and beta subunits only have one transcript, 0.5 kilobase (kb) long, whereas the genes for LH-I have two transcripts (0.5 and 2.6 kb). The small transcript (0.5 kb) is the mRNA only for LH-I beta and alpha polypeptides, whereas the large transcript (2.6 kb) codes for RC-L, RC-M, and the beta and alpha polypeptides of LH-I, as well as the product of an unknown open reading frame designated ORF C2397. These five genes thus comprise a single operon (designated the puf operon). The mRNA specifying the LH-II polypeptides is more abundant, more sensitive to changes in O2 concentration, and shows a variation over a wider range than that of the mRNA for LH-I, indicating that the genes for LH-II and LH-I/RC are regulated independently. The gene for RC-H (puhA) has at least two transcripts (1.2 and 1.4 kb) that initiate within ORF F1696 and respond differentially to light intensity. The expression of the genes coding for RC-L, RC-M, and RC-H is coordinately regulated by light intensity and O2 concentration. An increase in light intensity causes a decrease in the expression of the genes for LH-I, LH-II, and RC proteins. The genes coding for the enzymes in the bacteriochlorophyll biosynthetic pathways are regulated by light intensity and O2 in a manner similar to that of the genes for LH and RC proteins. The crt genes coding for the enzymes in carotenoid biosynthetic pathways, however, are regulated in an opposite fashion: high light intensity results in increased expression of crt genes. These results are interpreted based on the protective function of carotenoids under high light intensity in the presence of O2.